The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00425-018-2919-5
|View full text |Cite|
|
Sign up to set email alerts
|

Casein kinase 2 α and β subunits inversely modulate ABA signal output in Arabidopsis protoplasts

Abstract: Main conclusionOur transient gene expression analyses in Arabidopsis protoplasts support the view that CK2αs and CK2βs positively and negatively modulate ABRE-dependent gene expression, respectively.The phytohormone abscisic acid (ABA) regulates the expression of thousands of genes via ABA-responsive elements (ABREs), and has a crucial role in abiotic stress response. Casein kinase II (CK2), a conserved Ser/Thr protein kinase in eukaryotes, is essential for plant viability. Although the CK2 has been known as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…These findings support the hypothesis that the positive effect of CK2αs are much smaller than that of core ABA signaling components in ABA responses in the presence of exogenous ABA. Collectively, together with the previous findings that CK2β1 suppressed CK2α-mediated ABRE-dependent gene expression 21 and that CK2αs positively modulate ABRE-dependent gene expression dependently of the core ABA signaling pathway in the presence of exogenous ABA, 21 these data suggest that CK2αs may be implicated in CK2-meidated fine-tuning ABA signaing through the core ABA signaling pathway under stress conditions.
10.1080/15592324.2018.1525998-F0002Figure 2.CK2αs positively modulate ABA signaling during seed germination and ABA-responsive marker genes even under non-stressed conditions. (A) relative expression levels of each CK2α gene in the WT and CK2α4-RNAi in ck2α1/2/3 mutant ( ck2α1/2/3-4i) .
…”
supporting
confidence: 83%
See 4 more Smart Citations
“…These findings support the hypothesis that the positive effect of CK2αs are much smaller than that of core ABA signaling components in ABA responses in the presence of exogenous ABA. Collectively, together with the previous findings that CK2β1 suppressed CK2α-mediated ABRE-dependent gene expression 21 and that CK2αs positively modulate ABRE-dependent gene expression dependently of the core ABA signaling pathway in the presence of exogenous ABA, 21 these data suggest that CK2αs may be implicated in CK2-meidated fine-tuning ABA signaing through the core ABA signaling pathway under stress conditions.
10.1080/15592324.2018.1525998-F0002Figure 2.CK2αs positively modulate ABA signaling during seed germination and ABA-responsive marker genes even under non-stressed conditions. (A) relative expression levels of each CK2α gene in the WT and CK2α4-RNAi in ck2α1/2/3 mutant ( ck2α1/2/3-4i) .
…”
supporting
confidence: 83%
“…16,17 Recently, we have demonstrated that CK2α and β subunits inversely modulate ABRE-dependent gene expression as ABA signal output in ABA signaling in Arabidopsis cells. 21 Our results indicate that CK2α1 and CK2α2 positively modulate ABRE-dependent gene expression, whereas CK2β1 negatively modulates ABRE-dependent gene expression mediated by AREB-SnRK2 pathway and by CK2αs. 21 However, recent biochemical analyses suggest that CK2 negatively regulates ABA signaling through facilitating both SnRK2 degradation and SnRK2 interaction with PP2C.…”
mentioning
confidence: 55%
See 3 more Smart Citations